PENGARUH FAMILY CONTROL, SIZE, SALES GROWTH, DAN LEVERAGE TERHADAP PROFITABILITAS DAN NILAI PERUSAHAAN PADA SEKTOR PERDAGANGAN, JASA, DAN INVESTASI - Verawati Hansen (Business Accounting Review, 2014)
This study aimed to examine the affects of family control, size, and leverage towards profitability and value of the firm. Sampels were taken from 84 trades,services, and investment companies that listed in Indonesia Stock Exchange from 2009-2011. The main variable from this study was family control, while the control variables were size, sales growth, and leverage. There were two model analysis tested in this study. The first model used firm profitability that measured by ROA (Return on Assets)  as the dependent variable and the second one used firm’s value that measured by Tobin’s Q. As a result, family control had positive and significant affect on profitability and negative insignificant affect on firm’s value. While size had positive and significant influence towards profitability and firm’s value. On the other side, sales growth had positive and insignificant impact on profitability yet sales growth also had negative insignificant affect against firm’s value. Furthermore, leverage had positive insignificant influence on profitability and positive significant influence on firm’s value.